2017
DOI: 10.1080/09168451.2016.1263149
|View full text |Cite
|
Sign up to set email alerts
|

Two new triterpenoids from the roots of Pinus densiflora

Abstract: Chemical investigation of the roots of Pinus densiflora led to the isolation of two new triterpenoids, (24S)-3β-methoxy-24,25-epoxy-lanost-9(11)-ene (1) and 29-acetoxy-3α-methoxyserrat-14-en-21α-ol (2), together with three known serratene-type triterpenoids (3-5) and four known diterpenoids (6-9). Their structures were determined by spectroscopic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It indicated the presence of one double bond, a methoxy, and an oxirane ring at C‐12, C‐3, and C‐29/31 of 2 , respectively. A comparison of the NMR data of 2 with olean‐12‐en [53–58] revealed that the structures of the two compounds were very similar except for the presence of methoxy at C‐3 and oxirane at C‐29 position; consequently, new compound 2 was identified as a 3 β ‐methoxy‐29(31)‐oxirane olean‐12‐ene ( Supporting Information Figure S4‐S6).…”
Section: Resultsmentioning
confidence: 99%
“…It indicated the presence of one double bond, a methoxy, and an oxirane ring at C‐12, C‐3, and C‐29/31 of 2 , respectively. A comparison of the NMR data of 2 with olean‐12‐en [53–58] revealed that the structures of the two compounds were very similar except for the presence of methoxy at C‐3 and oxirane at C‐29 position; consequently, new compound 2 was identified as a 3 β ‐methoxy‐29(31)‐oxirane olean‐12‐ene ( Supporting Information Figure S4‐S6).…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of P. merkusii bark resulted in three triterpenoids (C1, C3, and C5) and two steroids (C2 and C4). In previous research, triterpenoids and steroids have been linearly detected in the Pinaceae family (Zullo and Adam 2002;Le Milbeau et al 2013;Otaka et al 2016). Compound C1 has been reported in Pinus bark, i.e., P. armandii (Fang et al 1991;Fang and Cheng 1992), P. luchuensis (Yamamoto et al 2011), P. contorta (Rowe et al 1972), P. strobus (Zinkel and Evans 1972), P. radiata (Weston 1973), P. taiwanensis (Cheng and Chao 1979), and P. roxburghii (Labib et al 2018), while compound C5 been reported in the bark of P. lambertiana (Rowe 1964).…”
Section: Chemotaxonomic Significancementioning
confidence: 96%
“…In addition, root terpenoids play a crucial role in the defense against herbivores and pathogens ( Sharma et al., 2017 ; Lackus et al., 2018 ). Previous studies have analyzed the VOCs of Pinus species including Pinus tabuliformis, Pinus bungeana, Cedrus deodara, Pinus thunbergii ( Ji and Ji, 2021 ) , Pinus densiflora ( Otaka et al., 2017 ), Pinus halepensis ( Blanch et al., 2007 ), Pinus mugo ( Celiński et al., 2015 ), Pinus sylvestris ( Szmigielski et al., 2011 ), Pinus massoniana ( Quan and Ding, 2017 ), with a majority of the studies focusing on needles rather than roots.…”
Section: Introductionmentioning
confidence: 99%
“…While few studies have focused on root terpenoids in tree species ( Kleiber et al., 2017 ; Otaka et al., 2017 ; Quan and Ding, 2017 ; Chang et al., 2021 ), there is a complete lack of knowledge on the relationship between root terpenoids and water deficit conditions. More importantly, it is currently unknown whether terpenoid biosynthesis mitigates or alleviates drought stress in tree species Pinus strobus .…”
Section: Introductionmentioning
confidence: 99%